Empowerment of The Elderly Through PKK Activities at RPTRA Manunggal, South Jakarta - Muslimah Muslimah; Irma Maria Dulame; Wedia Hastuti (CV. Global Cendekia Inti, 2026)
Community service activities play an important role in empowering communities, particularly in improving the health quality and well-being of elderly individuals. This study aims to describe the implementation and impact of Family Welfare Empowerment (PKK) activities conducted at RPTRA Manunggal, located on Jl. Impres No. 4 RT 004/02, South Petukangan, Pesanggrahan District, South Jakarta. The activities are routinely carried out once a month on the third Thursday, involving 90 elderly participants aged 60 years and above (83.33% regular participation). The program integrates health examinations, blood pressure and blood tests, elderly physical exercise, and healthy lifestyle education guided by PKK cadres and health professionals. This study employed a qualitative descriptive approach through direct interviews with key informants to explore their experiences and perceptions regarding the program. Quantitative evaluation yields an overall average program benefit score of 75.4%, indicating high effectiveness in enhancing elderly quality of life. Specifically, participants reported significant outcomes, including improved health condition control (87%), increased physical fitness (80%), enhanced healthy lifestyle knowledge (77%), elevated enthusiasm for social interaction (70%), and reduced loneliness (63%). The community-based health service program at RPTRA Manunggal contributes positively to improving elderly quality of life and demonstrates the importance of sustainable community empowerment through collaborative health promotion programs.